Museum Pusaka Keraton Kesepuhan Cirebon, Jawa Barat (Kajian Tentang Sejarah Koleksi Dan Potensinya Sebagai Sumber Belajar Sejarah Di SMA) - Nova Dena Putri Irawan; I Wayan Putra Yasa; I Wayan Pardi (Widya Winayata : Jurnal Pendidikan Sejarah, 2023)
Cirebon Kesepuhan Palace is one of the Islamic kingdoms in Indonesia that existed from the 14th century until Indonesian independence. The Cirebon Kesepuhan Palace also plays an active role in the spread of Islam on the island of Java, especially in the western regions. The development of the kingdom was getting bigger so that it could get friends for politics from various regions in Indonesia to kingdoms outside Indonesia. Cooperation with kingdoms outside Indonesia means that the Cirebon Kesepuhan Palace often receives gift items from allied kingdoms. Items that have high benefits for the Cirebon Kesepuhan Palace and have beautiful value to be seen by many people. These items are still there today. To protect the relics from the Cirebon Kesepuhan Palace, the local government proposed the creation of a museum. Until 2015 the Museum was approved to become a place for historical objects. The museum is called the Cirebon Kesepuhan Keraton Heritage Museum, even though the name is a heritage museum, the contents of the museum are not only heirlooms, but also cultural objects that have high artistic value. Most of the relics are about heirlooms and inherited weapons that can still be exhibited in museums. Museum collection objects related to culture, one of which is gamelan heritage objects, which until now have high cultural value in the minds of the public. These collections from the Cirebon Kesepuhan Palace Heritage Museum will make us feel the feel of the old royal era. Each collection on display has its own story that makes visitors feel the uniqueness of the museum. Keywords: Cirebon Kesepuhan Palace, Museum, Collection